From Micro to Macro Widening the Investigation of Diversity in the Tran-sition to Higher Education - Mikaël De Clercq; Ellen Jansen; Taiga Brahm; Elke Bosse (EARLI, 2021)
Transition into higher education (HE) remains at the forefront of policy and practice in education worldwide (Gale & Parker, 2014). Transition as a process (Nicholson, 1990) in which individuals move from one stage to another may cause stress and discomfort that possibly lead to negative outcomes. Transition into HE is a particularly challenging process for the student due to a large variety of difficulties and requirements which could impede study success (Trautwein & Bosse, 2017). Moreover, increasing student numbers and diversity in European HE have reinforced concerns about study success in general and the successful transition to university in particular (Abbott-Chapmann, 2006, 2011; Vossensteyn et al., 2015; Wolter, 2013). Consequently, it is important to further develop our understanding of factors that can contribute to a successful and less stressful transitions into higher education for a diverse student body. In this special issue, we go beyond considering individual factors, such as student characteristics (micro level). In addition to student diversity, we investigate the impact of the learning environment/ institution (meso level) and national educational policies (macro level). Each study contributes to this endeavour by connecting two of the three levels of higher education.